Experimental sanding analysis: Thick wall cylinder versus true triaxial tests - Younessi, Ahmadreza; Rasouli, Vamegh; Wu, B. (ISRM, 2012)
Using a true triaxial stress cell (TTSC) the authors performed several sanding tests on cubes of synthetically made samples. The samples prepared based on an established procedure developed in the laboratory. Samples, with a dimension of 100×100×100 mm3, were subjected to far-field stresses while increasing the pore pressure inside the cell. Sands were produced from a borehole in the sample centre. An experiment was conducted with anisotropic lateral stress to investigate the effect of stress anisotropy on sand production. By applying uniform lateral stresses, an experiment analogy to TWC was performed for comparison purposes. Comparison of the results of these two experiments demonstrated the importance of considering the intermediate stress component in sanding analysis. The results of these experiments are presented in this paper.